Development of a Problem-Based Learning Module on the Topic of Kingdom Plantae at Islamic Boarding Schools - Usilah, Siti Lala; Fathir, Akhmad (Lombok Institute, 2024)
This study aimed to develop an effective biology learning module based on Problem-Based Learning (PBL) for Kingdom Plantae, tailored to the educational needs of students in Islamic boarding school environments. The methodology employed was the Research and Development (R&D) approach using the 4-D model, encompassing the stages of definition, design, and Development, including validation by subject matter and media experts and readability evaluations by teachers and students. The validation results indicated high content and presentation viability, with overall validation scores of 95.74% from subject matter experts and 91.93% from media experts. Positive feedback was also received from teachers and students, suggesting the module's suitability and effectiveness in enhancing material comprehension. The primary limitations include the coverage of only one topic and the need for improvements in presentation techniques and graphic design.